A short, general, Suzuki–Miyaura coupling anchored approach to 3-alkenylbutenolides: total synthesis of akolactones A & B, hamabiwalactone B and ancepsenolide. Issue 21 (27th May 2015) - Vasamsetty, Laxmaiah; Khan, Faiz Ahmed; Mehta, Goverdhan
Abstract: An efficient and versatile synthesis of 3-alkenylbutenolides through direct Suzuki–Miyaura cross coupling reaction between preformed 3-halobutenolides and a range of readily accessible boronic acids has been devised. The coupling process exhibits good functional group compatibility and is preparatively viable. The methodology has been applied to achieve short syntheses of natural products rac -akolactones A & B and rac -hamabiwalactone B. The scope of the Suzuki–Miyaura reaction based protocol has been further amplified through the synthesis of 3, 3′-alkenyl- bis -butenolides by employing α, ω- bis -boronic acids as coupling partners and applied to a synthesis of bioactive natural product rac -ancepsenolide. Graphical abstract: